Israel against democracy - Hilla Dayan (Amsterdam Law Forum, 2011)
This op-ed highlights the recent anti-democratic legislation in Israel analyzing its causes and impact on Israel's democratic foundations. It argues for sustained support for the right of dissent and for human rights defenders in Israel/Palestine as well as for more effective international intervention to bring an end to the Israeli occupation and advance the causes of democracy and justice in the region.